O Perfil Profissional de Egressos do Curso de Psicologia da Universidade Metodista de São Paulo (2013-2015): avanços e fragilidades na formação de psicólogos. - OLIVEIRA, WILLIAM MACHADO DE (2018)
The day by day on labor market presents to Professional Psychologist and also to just-graduated, some complex situations that lead them to confront their knowledge, competencies and abilities developed during the Graduation one related to professional practice. Besides that, the quality of graduation aims to, according to current legislation, to contribute to development structure, social and economic of the country. Based on this context the objective of this study, by means of exploratory field research the professional profile of graduates by Psychology course from Universidade Metodista do Estado de São Paulo. Due to graduates’ perceptions of the period 2013 to 2015, check the correlation between training offered, along the graduation, based to Programa Pedagógico do Curso de Psicologia (PCC/2008) and its impact on the insertion of this group in the labor market. The data collection was carried out by means of invitation via email to 31 graduates and made operational via Google Forms. Of which, 31 valid answers were obtained. The choice of respondents, considering the sample established, followed to the discretion of sampling accessibility and data were analyzed from strategies analysis quantitative. The research instrument was built for this study and was made up of questions that aimed to characterize the participants, to investigate their perception about their academic formation and their professional insertion, besides raising their perceptions regarding the importance and the domain of professional competences. Analyzes were performed of Central tendency. The result signaled domain positive skills and professional biased clinical, however skills and abilities related to group psychology process organizational present weaknesses and need to be potentiated. Despite the course offer the egress the possibility to deal in other psychology areas, concluded that in its entirety the graduates are predominantly young 20 to 30 years gender female, walking in the against the valuation monetary by genre gaining more than men most of the tracks remuneration and work directly and indirectly in the clinic. Although the research presents some points in which some deep reflection is needed in graduated composition course, about 87,1% of the graduates point that the course has responded